Text Mining and Quantitative Research of Medical Service Policy: Sichuan Province as an Example - Zhang, Huiqin; Zhu, Liping; Zeng, Chen; Chen, Xudong (Frontiers in Public Health, 2021)
Abstract：The policy of medical service plays a leading role in the construction of the "Health China". This paper constructs a three-dimensional framework for text mining of medical service policy from the dimension of policy instruments, policy strength and medical service activity types, the Sichuan province is taken as an example,221 medical service policy documents issued by the government and related departments are selected as the research samples, and the policy instruments, policy strength and medical service activity types are analyzed by the ROST and the Nviv11.0 software. It is concluded that the Government needs to optimize the structure of policy instruments, to appropriately reduce the use of environmental policy instruments but increase demand-based policy instruments. It is necessary to strengthen the interaction among the various sub-policy instruments, and increase the use of financial services, fiscal taxes, overseas communications and strategic measures.The increase of the proportion of the implementation of the government policy is helpful to the acceleration of the policy landing,the further improvement of the supervision system and the safeguard mechanism of the three-medicine linkage development can improve the sustainability of the medical service policy,and further solve the problem of difficult and expensive to see a doctor.